An IoT-Enabled Smart Energy Monitoring System to Enhance Industrial Energy Efficiency - SUHAIMI, SHAMIL; Maizul Ishak (Progress in Engineering Application and Technology, 2025)
The industrial sector in Malaysia significantly contributes to the national economy but accounts for over 45% of the country’s electricity consumption, resulting in high operational costs and increased greenhouse gas emissions. This project presents the design and implementation of a Smart Energy Monitoring System tailored for industrial buildings to enable real-time, departmental-level energy consumption tracking. Leveraging Internet of Things (IoT) technology, the system integrates current and voltage sensors with an ESP32 microcontroller, transmitting data via Wi-Fi to the BLYNK smartphone application. The prototype effectively measures electrical parameters such as current, voltage, and power usage, providing users with intuitive visualization, anomaly detection, and notification features. Experimental results demonstrate the system’s accuracy in monitoring energy consumption and identifying inefficiencies, facilitating informed decision-making to optimize energy use. This cost-effective and user-friendly solution aligns with Malaysia’s energy efficiency goals, promoting sustainable industrial practices by reducing energy costs and environmental impact. The proposed Smart Energy Monitoring System represents a significant advancement in industrial energy management, addressing the challenges of rising energy demands through innovative IoT applications.